I was so mad - Mayer, Mercer, 1943- (New York : Golden Press, 1983)
A child tries a variety of ways to dissolve anger.
"A Golden book"--Cover.
K-3
Keywords: Children's stories, American; Anger -- Fiction; Anger -- Fiction